PENENTUAN PREMI ASURANSI BERJANGKA LAST SURVIVOR UNTUK KASUS DUA ORANG TERTANGGUNG - Sitepu, Sanfriska Br (STATMAT: Jurnal Statistika dan Matematika, 2021)
Insurance is an agreement between the insurance service company and the policyholder as the insured party. The insured party will pay the premium as agreed upon to the insurance service provider. Insurance in Indonesia has developed rapidly, one of which is the last survivor term insurance. In this study, the determination of the last survivor insurance premium with a tenor of 10 years for the case of two insured persons aged 70 and 20 years respectively using the Indonesian mortality table in 2019. The first case, the two insureds are male and the second case, the two insured are female. The determination of the last survivor life insurance premium is completed by first determining the cash value of the annuity and the single premium. Based on the results obtained, the value of the premium depends on gender and the interest rate. Where, men pay premiums more expensive and the greater the interest rate, the smaller the value of the premium to be paid